Intruder detection - Muhamad Haffiz, Muhamad Adlin (2013)
With the increasing case in the robbery now day, it relevant to develop a security system that can protect the house of the victim, intruder detection system is a security system that use a mini computer Raspberry pi to detect an intruder that bypass the house of the user, most of the robbery happen when the victim is away with a reason of holiday or work, with the current security system that cannot by effort by some victim, intruder detection system is a security system that been develop with a low budget but with a efficient result, it will inform the victim by sending Short Message Service(SMS) if an intruder been detected inside the victim house. It been develop using the minicomputer raspberry pi and several alarm hardware such as magnetic switch and movement sensor that been assemble together to form an security system that can be effort by everyone, develop using PHP and python programming user can determine where they want to place the alarm and what kind of message that they will receive if there an intruder in the house thus protecting the user house by giving the user to inform to the authority such as police or the neighbor to check their house.